2011
DOI: 10.1002/jms.2000
|View full text |Cite
|
Sign up to set email alerts
|

Reflectron MALDI TOF and MALDI TOF/TOF mass spectrometry reveal novel structural details of native lipooligosaccharides

Abstract: Lipooligosaccharides (LOS) are powerful Gram-negative glycolipids that evade the immune system and invade host animal and vegetal cells. The structural elucidation of LOS is pivotal to understanding the mechanisms of infection at the molecular level. The amphiphilic nature of LOS has been the main obstacle for structural analysis by matrix-assisted laser desorption/ionization (MALDI) mass spectrometry (MS). Our approach has resolved this important issue and has permitted us to obtain reflectron MALDI mass spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
58
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 46 publications
(60 citation statements)
references
References 42 publications
1
58
0
1
Order By: Relevance
“…1B). It is worth noting that this information was achieved directly on the intact LPS molecule; in fact, the lipid A MS spectrum was directly obtained on the intact LPS upon in source fragmentation obtained in our optimized conditions (33); in this way, we can exclude any chemical change in lipid A as a result of chemical treatment. In aLPS, the canonical hexaacylated lipid A species was highly prevalent (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1B). It is worth noting that this information was achieved directly on the intact LPS molecule; in fact, the lipid A MS spectrum was directly obtained on the intact LPS upon in source fragmentation obtained in our optimized conditions (33); in this way, we can exclude any chemical change in lipid A as a result of chemical treatment. In aLPS, the canonical hexaacylated lipid A species was highly prevalent (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…D'Hauteville et al (28) reported that WT S. flexneri serotype 5 (M90T, the same strain as in the present study) possessed a predominantly hexaacylated lipid A (93%). MALDI TOF/TOF MS performed on LPS of a S. flexneri 5 M90T revealed the presence of lipid A isoforms with the major component being the hexaacylated lipid A, with minor peaks being attributed to pentaacylated and tetraacylated species (33).…”
Section: Discussionmentioning
confidence: 99%
“…Using a thin-layer matrix composed of THAP and nitrocellulose [31], intact LOS can be analyzed by MALDI MS, generally in the negative-ion mode [9,10,12,13,[30][31][32]35]. This method produces an envelope of (M-H) -ions, as well as informative prompt fragments arising from the lipid A and oligosaccharide domains of the molecule.…”
Section: Molecular Weight Profiling Of Intact Losmentioning
confidence: 99%
“…Prompt fragments representing both domains of the molecule corroborate proposed compositions of the LOS molecular ions detected. Although previously only conducted in linear mode, analysis of intact LOS by high-resolution, reflectron mode MALDI-TOF MS has now been achieved [12,13,32,35]. The ability to measure monoisotopic molecular ions with good mass accuracy (<20 ppm) has dramatically improved the quality of the information that can be obtained from MALDI-TOF MS analysis of intact LOS.…”
mentioning
confidence: 99%
“…특히 지질 A의 구조에 있어서 아실 사슬 (acyl chain)의 위치와 개수 및 인산기의 존재 유무가 내독소 활성에 큰 영향을 끼친다 [12]. 지질 A 구조 분석을 위한 선행 연구들에 있어서는, 핵자기공명 분광기 (nuclear magnetic resonance (NMR) spectroscopy) [13], 전기분무 질량분석기 (electrospray ionization coupled tandem mass spectrometry (ESI-MS/MS)) [14], 모세관 전기영동 질량분석기 (capillary electrophoresis-mass spectrometry (CE-MS)) [15], 및 매트릭스 보조 이온화/탈착 질량분석기 (matrix-assisted laser ionization/desorption time-of-flight mass spectrometry (MALDI-TOF MS)) [16] Fig. 1(a)) [20][21][22][23].…”
unclassified